WELDING TECHNICAL CLINIC ANALYSIS OF WELDING SMAW WELDING IN VEHICLES OF DISTORTION RECESSING - Heri Wibowo; Riswan Dwi Jatmiko (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
Contplicated distortion alu,ays )tappens in metel melting and.freezirtg proL'ess on welding Lip trt now, the common merhod to recluce distnrtion are; base ntetal prehettling, heat irtput minirualization, welding process sequence, etc. the last has been u,setJ l:y tr'r,Uort, hov:ettet' lhe sequence ofbest effectivitlt and elficiency has not been yet studied. This research aims to lnow ffict of welding process sequence b), sttrdied 5 dil/brent v,elding route related to angle distortion (a), bending distortion (0), c'ross distortian (LI .l anci atial distortion (LP). 'tilelding process used sltielded metal arc welding, base metal ofST 37 and electrode of E6013; 2.6 mm and 3.2 mm of diameter. Fou'kinds oJ te,st used ungle gauge oJ 0.lo precision ctnd caliper of 0.05 mm precision.Based on the test, it could be known that the lov:est angle distortion toctk pluc:e on 3 tirues roule that was 3.07